PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SISTEM PERNAPASAN MANUSIA DI KELAS XI SMA SWASTA KARTIKA I-4 PEMATANGSIANTAR TAHUN AJARAN 2021/2022 - Asriyati, Dewi; Wilson Sitopu, Joni; Rosenta Purba, Ika (Jurnal Metabio, 2022)
This study aims to determine the differences in student learning outcomes and the magnitude of the differences in student learning outcomes using the problem-based learning model and conventional methods on the human respiratory system material in grade XI of SMA Swasta Kartika I-4 Pematangsiantar in the 2021/2022 academic year. The population was 193 students consisting of 4 classes and the sample was taken using cluster random sampling to obtain 2 classes: the experimental class (XI mia 1) with 48 students and the control class (XI mia 3) with 48 students. The experimental class was treated using the problem-based learning model and the control class was treated using the conventional method. Data analysis was carried out by finding the average (X̅ ), standard deviation (S) and hypothesis testing (t-test) at a significance level of α = 0.05. From the results of the study, the average post-test score for the experimental class was 83.02 and the control class was 80.10 with a difference in learning outcomes of 2.29. From the results of the hypothesis testing (t-test), the calculated t (2.721 > t table (1.985) was obtained at a significance level of α = 0.05 and degrees of freedom (df) = 94, so Ho is rejected and Ha is accepted, meaning there is a difference in student learning outcomes using the problem-based learning model and the conventional method on the human respiratory system material in grade XI of SMA Swasta Kartika I-4 Pematangsiantar in the 2021/2022 academic year. It was concluded that there is a difference in student learning outcomes using the problem-based learning model and the conventional method on the human respiratory system material in grade XI of SMA Swasta Kartika I-4 Pematangsiantar in the 2021/2022 academic year.